Rentowność działalności powszechnych towarzystw emerytalnych w Polsce - Trippner, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
In Poland since 1999, there has been in operation a reformed national insurance system whose main elements are pension insurances. Its construction is based on three insurance pillars. The most important parts of this system are second obligatory capital pillar and pension companies that manage and supervise individual accounts in open pension funds. The author focuses on effectiveness of pension companies and attempts to answer the question, whether all companies are profitable and which factors determine the level of profits. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 568-577